(untitled) (Modern education and development, 2025)
The pathogenetic aspects of the hypothalamo-pituitary syndrome in patients with epilepsy is a very complex and multifaceted problem, which requires the study of the interaction of the nervous system and the endocrine system at different levels. This article provides information on the pathogenetic mechanisms of hypothalamo-pituitary syndrome associated with epilepsy, clinical manifestations, diagnostic and treatment methods. Epilepsy is a disease that contributes to the involvement of the patient’s brain in the pathological process as a single functional system. In turn, a violation of the functional state of the patient’s brain leads to an imbalance in the activity of nonspecific systems and manifests itself not only in electroencephalographic features, but also in characteristic disorders in the cognitive, mental and vegetative status of the patient.